Solving taxonomic and nomenclatural problems among the Neotropical species of the family Mantispidae (Insecta, Neuroptera) - Renato Jose Pires Machado; Hongyu Li; Michael Ohl (Deutsche Entomologische Zeitschrift, 2025)
The present study focuses on solving some dubious species-group names in Neotropical Mantispidae (Insecta, Neuroptera). We analyzed type specimens deposited in European museums that were not available in recent taxonomic studies on the family. A total of 28 names were discussed here which resulted in 14 new synonyms and six new combinations. Four names are considered as nomina dubia. Ten lectotypes are designated. High resolution images of the type specimens of 19 species are provided here.